From energy to electron transfer photocatalysis (PenT → PET): oxidative cyclobutane cleavage alters the product composition. Issue 93 (4th November 2022) - Lefarth, Jens; Haseloer, Alexander; Kletsch, Lukas; Klein, Axel; Neudörfl, Jörg; Griesbeck, Axel G.
Abstract : Photocatalytic [2+2]-cycloadditions between enones and electron-rich enol ethers are initiated by triplet–triplet energy transfer. In a consecutive step, photoinduced electron transfer leads to oxidative isomerization of the cyclobutane products. Abstract : Photocatalytic [2+2]-cycloadditions between cyclic enones and electron-rich cyclic enol ethers are initiated by triplet–triplet energy transfer from an excited iridium photocatalyst to the enone acceptor. The composition of the resulting cycloadduct mixture shows a surprising time dependency of the cyclobutane stereoisomeric ratio which indicates that the products are not photostable under the reaction conditions. The isomerisation of the cycloadducts 3 by a photoinduced redox process points to a switch from triplet energy transfer (PenT) to photoinduced electron transfer (PET) catalysis.